Activation of bivalent factor DLX5 cooperates with master regulator TP63 to promote squamous cell carcinoma. Issue 16 (9th August 2021) - Huang, Yongsheng; Yang, Qian; Zheng, Yueyuan; Lin, Lehang; Xu, Xin; Xu, Xiu-E; Silva, Tiago C; Hazawa, Masaharu; Peng, Li; Cao, Haotian; Ding, Yanbing; Lu, Daning; et al.
Abstract: To reconstruct systematically hyperactive transcription factor (TF)-dependent transcription networks in squamous cell carcinomas (SCCs), a computational method (ELMER) was applied to 1293 pan-SCC patient samples, and 44 hyperactive SCC TFs were identified. As a top candidate, DLX5 exhibits a notable bifurcate re-configuration of its bivalent promoter in cancer. Specifically, DLX5 maintains a bivalent state in normal tissues; its promoter is hypermethylation, leading to DLX5 transcriptional silencing in esophageal adenocarcinoma (EAC). In stark contrast, DLX5 promoter gains active histone marks and becomes transcriptionally activated in ESCC, which is directly mediated by SOX2. Functionally, silencing of DLX5 substantially inhibits SCC viability both in vitro and in vivo . Mechanistically, DLX5 cooperates with TP63 in regulating ∼2000 enhancers and promoters, which converge on activating cancer-promoting pathways. Together, our data establish a novel and strong SCC-promoting factor and elucidate a new epigenomic mechanism - bifurcate chromatin re-configuration - during cancer development.